2017
DOI: 10.1002/acm2.12145
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetric and radiobiological comparison for quality assurance of IMRT and VMAT plans

Abstract: IntroductionThe gamma analysis used for quality assurance of a complex radiotherapy plan examines the dosimetric equivalence between planned and measured dose distributions within some tolerance. This study explores whether the dosimetric difference is correlated with any radiobiological difference between delivered and planned dose.Methods VMAT or IMRT plans optimized for 14 cancer patients were calculated and delivered to a QA device. Measured dose was compared against planned dose using 2‐D gamma analysis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…There are precedence available in the literature. In a 2017 study on patient‐specific QA of IMRT plans, 2D gamma analysis alone could not assure radiobiological equivalence between planned and delivered dose . The authors concluded that radiobiological analysis in addition to physical dose comparison may provide adequate patient‐specific QA of IMRT plans.…”
Section: Discussionmentioning
confidence: 99%
“…There are precedence available in the literature. In a 2017 study on patient‐specific QA of IMRT plans, 2D gamma analysis alone could not assure radiobiological equivalence between planned and delivered dose . The authors concluded that radiobiological analysis in addition to physical dose comparison may provide adequate patient‐specific QA of IMRT plans.…”
Section: Discussionmentioning
confidence: 99%
“…The comparison of multi-types of radiotherapy plans using the radiobiological evaluation has been published in research ( Puzhakkal et al, 2016 ; Chow et al, 2020 , Rehman et al, 2018 , Kim et al, 2018 , Paudel et al, 2017 ). In 2016, Puzhakkal et al employed radiobiological techniques to confirm the treatment of 30 patients with head and neck and brain tumors as well as prostate cancers.…”
Section: Introductionmentioning
confidence: 99%
“…Limited statistically significant differences existed in either biological or physical dosage indices of the healthy nearby organs. Paudel et al examined IMRT and VMAT plans for quality assurance using the assessment method ( Paudel et al, 2017 ). They suggested that the radiobiological analysis should be considered for the assessment of complex radiotherapy plans.…”
Section: Introductionmentioning
confidence: 99%
“…9 The commercially available dosimetry systems, such as ionisation chamber, film and PSQA phantom, can be used for the PSQA procedure. 10 These dosimetry systems are integrated with software that analyses the outcome with TPS dose calculation in three-dimension is now widely used in the PSQA of VMAT. These dosimetry systems have been recommended by the AAPM Task Group 218.…”
Section: Introductionmentioning
confidence: 99%